Critical Analysis and Optimization of Stoichiometric Ratio of Drug-Coformer on Cocrystal Design: Molecular Docking, In Vitro and In Vivo Assessment - Manami Dhibar; Santanu Chakraborty; Souvik Basak; Paramita Pattanayak; Tanmay Chatterjee; Balaram Ghosh; Mohamed Raafat; Mohammed A. S. Abourehab (MDPI AG, 2023)
In this present research, an attempt has been made to address the influence of drug-coformer stoichiometric ratio on cocrystal design and its impact on improvement of solubility and dissolution, as well as bioavailability of poorly soluble telmisartan. The chemistry behind cocrystallization and the optimization of drug-coformer molar ratio were explored by the molecular docking approach, and theoretical were implemented practically to solve the solubility as well as bioavailability related issues of telmisartan. A new multicomponent solid form, i.e., cocrystal, was fabricated using different molar ratios of telmisartan and maleic acid, and characterized by SEM, DSC and XRD studies. The molecular docking study suggested that specific molar ratios of drug-coformer can successfully cluster with each other and form a specific geometry with favourable energy conformation to form cocrystals. Synthesized telmisartan-maleic acid cocrystals showed remarkable improvement in solubility and dissolution of telmisartan by 9.08-fold and 3.11-fold, respectively. A SEM study revealed the formation of cocrystals of telmisartan when treated with maleic acid. DSC and XRD studies also confirmed the conversion of crystalline telmisartan into its cocrystal state upon treating with maleic acid. Preclinical investigation revealed significant improvement in the efficacy of optimized cocrystals in terms of plasma drug concentration, indicating enhanced bioavailability through improved solubility as well as dissolution of telmisartan cocrystals. The present research concluded that molecular docking is an important path in selecting an appropriate stoichiometric ratio of telmisartan: maleic acid to form cocrystals and improve the solubility, dissolution, and bioavailability of poorly soluble telmisartan.